Stretchable conductive elastomer for wireless wearable communication applications - Zhibo Chen (Nature Portfolio, 2017)
Abstract Wearable devices have provided noninvasive and continuous monitoring of physiological parameters in healthcare applications. However, for the comfortable applications of wearable devices on human body, two key requirements are to replace conventional bulky devices into soft and deformable ones and to have wireless wearable communication. In this paper we present a simple, low-cost and highly efficient all-elastomeric conductor that can be used in a soft radio-frequency (RF) transmission line and antenna. We show a stretchable transmission line and two stretchable antennas fabricated with conventional screen printing. The stretchable conductor used in this fabrication method, which is a mixture of Ag and Polydimethylsiloxane (PDMS), can be stretched at high strains while maintaining a high conductivity, low attenuation and feasible radiation performance. The measured conductivity of the stretchable conductor reaches 1000 S/cm. Additionally, the highly conductive printed Ag-PDMS is utilized to construct transmission lines and antennas. The performance of these stretchable components, especially under different conditions of bending, stretching and twisting, are experimentally examined in common wireless-communication frequency bands. Our results demonstrate that printed Ag-PDMS enabled RF passive components have the desired property and quality for wireless wearable communication applications, which would provide new opportunities for wearable healthcare electronics.